2013
DOI: 10.1177/0092055x13507782
|View full text |Cite
|
Sign up to set email alerts
|

The Perceived Benefits of a Preparing Future Faculty Program and Its Effect on Job Satisfaction, Confidence, and Competence

Abstract: The training of effective instructors and future faculty members is a critical component of doctoral programs in sociology. Many universities and departments have instituted a single course, course sequence, or certification program dedicated to the preparation of future academic faculty. This article evaluates the efficacy of one such program, and asks two questions: (1) What are the most useful aspects of the Preparing Future Faculty (PFF) program? (2) Is participation in the PFF program associated with grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 13 publications
4
16
0
Order By: Relevance
“…Although efforts to improve postsecondary instruction generally have focused on current faculty, more attention is being given to how future faculty 1 are being prepared to assume academic roles and responsibilities (e.g., Wulff and Austin, 2004 ; Hopwood and Stocks, 2008 ; Austin, 2010 ; Schönwetter and Ellis, 2010 ; Hershock et al ., 2011 ; Kalish et al , 2011 ; Palmer, 2011 ; Wurgler et al , 2013 ). Doctoral training in STEM fields has traditionally consisted of a doctoral student working closely with a faculty advisor to learn the research methods and content knowledge that are constitutive of the discipline ( Walker et al , 2008 ; Anderson et al , 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although efforts to improve postsecondary instruction generally have focused on current faculty, more attention is being given to how future faculty 1 are being prepared to assume academic roles and responsibilities (e.g., Wulff and Austin, 2004 ; Hopwood and Stocks, 2008 ; Austin, 2010 ; Schönwetter and Ellis, 2010 ; Hershock et al ., 2011 ; Kalish et al , 2011 ; Palmer, 2011 ; Wurgler et al , 2013 ). Doctoral training in STEM fields has traditionally consisted of a doctoral student working closely with a faculty advisor to learn the research methods and content knowledge that are constitutive of the discipline ( Walker et al , 2008 ; Anderson et al , 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…While Davis & Newstrom (2010) revealed that an employee will feel satisfied if he gets a reward commensurate with what is expected and in accordance with the aspirations and abilities he has. According to Wurgler, VanHeuvelen, Rohrman, Loehr, & Grace (2014) high job satisfaction affects the perceptions of competency of study participants. Performance theory is closely related to competency theory and has three basic principles of competence including expertise, experience, and knowledge, and various cognitive abilities (Boyatzis & Boyatzis, 2008).…”
Section: Job Satisfactionmentioning
confidence: 99%
“…Furthermore, Wurgler, VanHeuvelen, Rohrman, Loehr, and Grace () examined the impact of the University of Indiana's Sociology Department's PFF initiatives on job satisfaction, confidence, and competence of its graduates. When comparing those graduate students who completed a three‐course sequence to those who did not (including those who may have taken only the first course in teaching), the PFF participants reported lower levels of job satisfaction but higher confidence in their first teaching assignments, although not statistically significant.…”
mentioning
confidence: 99%
“…Although research has been conducted recently to provide a sense of the current landscape of PFF programs (Connolly et al, ; Palmer, ) and the impact of one institutional PFF program on participants' job satisfaction and competence (Wurgler et al, ), there are still many more questions to be answered with regard to PFF offerings. For example, what are the career outcomes for graduate students who participate in PFF programs?…”
mentioning
confidence: 99%